Implementation of Podcast Media for Social Education in Pesantren - Martanti, Fitria; Maskur, Maskur; Fatkhuronji, Moch (Sekolah Tinggi Agama Islam Sumatera Medan, 2026)
Learning in pesantren is often perceived as a traditional system that lags behind modern educational institutions. However, various digitalization efforts have been undertaken as a form of adaptation to the advancement of science and technology. Nevertheless, studies on podcast-based learning in pesantren remain limited. This study aims to analyze the implementation of podcast-based learning, its implications for the learning process, and the challenges faced at Pesantren Darul Ilmi. This research employs a qualitative approach, with data collected through interviews, observations, and documentation involving the pesantren leader, assistant teachers, and students. Data analysis was conducted through data reduction, data display, and conclusion drawing. The findings reveal that podcast-based learning functions as a complementary medium that supports conventional methods such as lectures, simulations, and role-playing. Its implications include enhancing students’ knowledge, strengthening social education, and expanding the promotion of the pesantren through digital media. However, its implementation still faces limitations in resources and the absence of dedicated management. These findings highlight the importance of strengthening management systems to ensure the sustainability of digital learning innovation in pesantren.